Penerapan Audit Kas dan Setara Kas Sebagai Strategi Efektivitas Manajemen Keuangan Perusahaan (Lembaga Pengembangan Kinerja Dosen, 2025)
This research discusses the effectiveness of cash and cash equivalents audits in relation to the improvement of corporate financial management strategies. Cash and cash equivalents are crucial accounts in financial statements because they are directly related to liquidity and the sustainability of company operations. This study uses a qualitative descriptive approach with data collection techniques through interviews, documentation, and literature studies. The research findings indicate that audits of cash and cash equivalents conducted according to standards not only serve to ensure the reliability of financial statements but also provide strategic contributions to the company. Effective audits can improve transparency, strengthen internal controls, and provide accurate financial information as a basis for formulating financial management strategies.